Romance and exemplarity in post-war Spanish women's narratives - Kebadze, Nino, 1975- (Colección Támesis. Monografías ;, 2009)
The effects of General Francisco Franco's authoritarian rule (1939-1975) on the production and reception of cultural texts can be gauged by the silence that now surrounds them. This is especially true of works which enjoyed considerable popularity when fi.